Gratitude Affects Inter-Subjective Synchronicity for Cognitive Performance and Autonomic Responsiveness - Balconi, Michela; Fronda, Giulia (Frontiers in Psychology, 2021)
Recently, social neurosciences have been interested in the investigation of neurophysiological responses related to the experience of positive emotions, such as gratitude, during social interactions. Specifically, the aim of the present research was to investigate whether gratitude related to gift exchange could favor cooperative behavior and bond construction, by improving behavioral and autonomic responsivity. At this regard, the autonomic synchronization and behavioral performance of 16 friends coupled in dyads were recorded during a joint attentional task. Gift exchange could occurred either at the beginning or in the middle of the task. For the recording of simultaneous autonomic activity (heart rate, HR; skin conductance level, SCL), a hyperscanning biofeedback paradigm was used. Intra-subjective analysis showed an increase in behavioral (accuracy - ACC) and autonomic responses (HR, SCL) when the gift exchange took place at the beginning of the task rather than in the middle. Moreover, inter-subjective analysis revealed an increase in behavioral performance and greater autonomic synchronization of HR index. The present research, therefore, shows how gratitude and trust experienced following gift exchange can modify participants’ reactions by creating a shared cognition and the adoption of joint strategies.